1977
DOI: 10.1139/v77-217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 13C and 1H N-alkyl shifts of isomeric alkyl tetrazoles: some ambident benzylations

Abstract: 13C nmr alkyl shifts of N-alkyl tetrazoles and azoles follow the pattern of proton shifts. The shielding of the N-alkyl group increases for the structural units[Formula: see text]The carbon spectra are more reliable for structural assignment. Syntheses of a number of mono- and dibenzyl derivatives of benzaldehyde tetrazol-5-ylhydrazone are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…N-1 and N-2 isomeric tetrazoles can be readily distinguishable by their 1 H and 13 C NMR spectra. According to Butler 21 and others, 18,22 C-5 resonates at ca. d 150 ppm for N-1 tetrazole and at ca.…”
Section: Synthesismentioning
confidence: 98%
“…N-1 and N-2 isomeric tetrazoles can be readily distinguishable by their 1 H and 13 C NMR spectra. According to Butler 21 and others, 18,22 C-5 resonates at ca. d 150 ppm for N-1 tetrazole and at ca.…”
Section: Synthesismentioning
confidence: 98%
“…0.15-0.35 ppm in the 1 H spectra and by ca. 2-6 ppm in the 13 C spectra to their corresponding N-2 isomers 9 . The regioselectivity in the alkylation was confirmed by the analysis of the 13 C NMR chemical shifts of the carbon atom C5 in the tetrazole ring.…”
Section: Phenyltetrazole Ligandsmentioning
confidence: 98%
“…The observed difference of the chemical shifts for the two isomeric compounds calculated as Δδ = δ2,5-isomer − δ1,5-isomer lies in the range of 10.6-12.0 ppm [26,28,29]. Moreover, it has been also shown that the 13 C-NMR chemical shifts of tetrazole N-Cα (TN-Cα) carbon atom of 2,5-disubstituted tetrazoles are higher compared to the corresponding resonances in the 1,5-disubstituted isomers [10,26,31,32]. Therefore, comparison of 13 C-NMR data of 2, 3, 6, 9 and 10 with those presented for 2,5-and 1,5-disubstituted tetrazoles allows unambiguously identifying and differentiating isomeric N-1-and N-2-substituted tetrazoles.…”
Section: Determination Of the Structure Of The Bromide 2 And The Intementioning
confidence: 99%